Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1101/2021.11.04.467197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D reconstruction of cell nuclei in a full Drosophila brain

Abstract: We reconstructed all cell nuclei in a 3D image of a Drosophila brain acquired by serial section electron microscopy (EM). The total number of nuclei is approximately 133,000, at least 87% of which belong to neurons. Neuronal nuclei vary from several hundred down to roughly 5 cubic micrometers. Glial nuclei can be even smaller. The optic lobes contain more than two times the number of cells than the central brain. Our nuclear reconstruction serves as a spatial map and index to the cells in a Drosophila brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…We then used CNNs to segment the dataset into neurons and fragments of neurons and to predict synapse locations (Figure 1C; (Macrina et al, 2021)), as well as pre-and post-synaptic partners (Buhmann et al, 2020). To identify all cells intrinsic to the VNC, we detected nuclei using another CNN (Figure 1E-F and methods; (Lee et al, 2017;Mu et al, 2021)), which identified 17,076 putative cells. Through manual inspection, we classified 14,621 of these nuclei as neuronal (85.6%), 2,030 as glial (11.9%), and 425 as false positives (2.5%) (Figure S1).…”
Section: Automated Reconstruction and Tools For Analysis Of An Em Vol...mentioning
confidence: 99%
“…We then used CNNs to segment the dataset into neurons and fragments of neurons and to predict synapse locations (Figure 1C; (Macrina et al, 2021)), as well as pre-and post-synaptic partners (Buhmann et al, 2020). To identify all cells intrinsic to the VNC, we detected nuclei using another CNN (Figure 1E-F and methods; (Lee et al, 2017;Mu et al, 2021)), which identified 17,076 putative cells. Through manual inspection, we classified 14,621 of these nuclei as neuronal (85.6%), 2,030 as glial (11.9%), and 425 as false positives (2.5%) (Figure S1).…”
Section: Automated Reconstruction and Tools For Analysis Of An Em Vol...mentioning
confidence: 99%
“…D. melanogaster have around 25,000 cells in the CB (Scheffer et al 2020;though Mu et al 2022 (90,000 in Mu et al 2022;107,000 in Raji & Potter 2021) are much lower than the 250,000 and 320,000 cells in the OLs of female and male H. illucens, respectively. OL cell nuclei were noticeably smaller than those in the CB (Figure 1) similar to D. melanogaster (Mu et al 2022).…”
Section: Discussionmentioning
confidence: 69%
“…melanogaster (most D. melanogaster counts range from 93,000 through 133,000; Godfrey et al 2021, Scheffer et al 2020, Mu et al 2022; but some estimate 208,000 cells, Raji & Potter 2021). The vast majority of this increase in cell number is likely due to the optic lobes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They visualize nuclei distributions using 3D histograms and their locations using 2D multi‐axis views. For the purpose of nuclei analysis and model training, Lin et al [LWP * 21] and Mu et al [MYT * 21] provide a dataset containing around 170,000 nuclei segmentations.…”
Section: Visual Exploration and Analysismentioning
confidence: 99%